Barriers and Facilitators toward HIV Testing and Health Perceptions among African-American Men Who Have Sex with Women at a South Side Chicago Community Health Center: A Pilot Study - Cooke, Ian J.; Jeremiah, Rohan D.; Moore, Nataka J.; Watson, Karriem; Dixon, Michael A.; Jordan, Gregory L.; Murray, Marcus; Keeter, Mary K.; Hollowell, Courtney M. P.; Murphy, Adam B. (Frontiers in Public Health, 2017)
In the US, African Americans (AA) HIV infection rates are higher than any other racial group, and AA men who have sex with women (MSW) are a significant proportion of new cases. There is little research into AA MSW HIV/AIDS knowledge, barriers and facilitators of HIV testing in Chicago. We enrolled a convenience sample of AA MSW from a community health clinic who completed self-administered surveys assessing HIV knowledge and testing-related barriers and facilitators. The survey was a combination of questions from several validated instruments and additional questions were written based on key informant interviews with social scientists to tailor the questionnaire for AA men living on the Southside of Chicago. We recruited 20 AA MSW (mean age 47.4 years). Sixty-five percent had incomes <10,000/year, 30% were insured and 50% had post-secondary education. Despite low socioeconomic status, their HIV literacy was relatively high. The identified major barriers to testing were low perceived HIV risk, concerns over privacy and external stigma at testing sites. Future efforts should focus on educating AA MSW on actual risk for HIV and address issues of privacy and stigma at testing sites.